Projeto - Cantando a gente brinca, brincando a gente aprende - Soares, Corina; Atayde, Joselda de Oliveira; Foresti, Nélci; Oliveira, Maria Auxiliadora de; Santos, Marlene Alves dos; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> VER PDF